Computing essentials : making IT work for you - O'Leary, Timothy J.; O'Leary, Linda I.
"Computing Essentials 2014 provides you with a complete learning solution focusing on the most important, essential, and current concepts of information technology. Students are given a streamlined, concise, relevant approach to the fundamental issues surrounding the world of computing through a balance between theory and applied learning of these important topics. Overall, all of the items featured with this text --including the end-of-chapter materials and the text Web sit-work together to help students truly understand the basics of computer concepts." --Publisher's website
Includes index
Keywords: Computers; Electronic data processing